Community Participation In Development Of Environmental Impact Analysis Documents (AMDAL) Based On Arnstein Concept - Prita Hapsari Kertaningrum; Widayati Widayati (Law Development Journal, 2021)
With the enactment of Act No. 11 of 2020 concerning Job Creation, Act No. 32 of 2009 concerning Environmental Protection and Management underwent changes, so that one of the main changes is community participation in the process of preparing the Environmental Impact Analysis (AMDAL) document. This article examines community participation in the preparation of the AMDAL document based on the Job Creation Act according to the concept of community participation by Arnstein. With a normative juridical approach, it can be concluded that community participation in the preparation of AMDAL documents according to the Job Creation Law is included in the second level (Tokenism) meaning that public participation is limited in the form of submitting suggestions, opinions and responses but there is no guarantee that the opinions expressed will be considered in decision-making.